Plan de marketing para la comercialización de hortalizas orgánicas del grupo de hojas del centro experimental La Playita en el cantón La Maná provincia de Cotopaxi año 2012-2016 - Triana Brito, Marjorie Alexandra (2014)
This investigative work was originated with the aim to know the feasibility for the design of a Marketing Plan that contributes to the promotion of the advantages and profits that offer the sheets group organic vegetables from “La Playita” Experimental Center, for the benefit of the consumers in La Maná cantón, Cotopaxi Province during the period 2012- 2016. It was used the descriptive, exploratory, correlational and explicative research, a lot of information was collected from the consuming population of this kind of vegetables by using surveys, for the proposal of elaborating a Marketing Plan to commercialize the sheets group organic vegetables, showing the following results: sheets group organic vegetables unsatisfied demand equal to 541.729,51 kg during the first year of project execution, that is why it is required the application of P’s strategies, as a economic study to profit this demand to get of 56.104,85 kg....